Anxiety and clinical outcomes of patients with acute coronary syndrome: a meta-analysis - Jie Li; Chuanjun Zhuo; Feng Ji; Junxian Song; Xiangyang Gao; Deguo Jiang; Guangdong Chen; Suling Chen; Xiaodong Lin (BMJ Open)
Objectives Anxiety has been suggested to be associated with poor outcomes in patients with acute coronary syndrome (ACS). However, results of previous follow-up studies were inconsistent. The aim of this meta-analysis was to evaluate the association between anxiety and clinical outcomes in patients with ACS, and to investigate the potential role of depression underlying the above association.Design A meta-analysis of prospective follow-up studies.Setting Hospitals.Participants Patients with ACS.Interventions We included related prospective follow-up studies up through 20 July 2019 that were identified by searching PubMed and Embase databases. A random-effect model was used for the meta-analysis. Anxiety was evaluated by validated instruments at baseline.Primary and secondary outcome measures We determined the association between anxiety and risks of mortality and adverse cardiovascular events (MACEs) in patients with ACS.Results Our analysis included 17 studies involving 39 038 patients wqith ACS. Anxiety was independently associated with increased mortality risk (adjusted risk ratio (RR) 1.21, 95% CI 1.07 to 1.37, p=0.002) and MACEs (adjusted RR 1.47, 95% CI 1.24 to 1.74, p<0.001) in patients with ACS. Subgroup analyses showed that depression may at least partly confound the association between anxiety and poor outcomes in patients with ACS. Adjustment of depression significantly attenuated the association between anxiety and MACEs (adjusted RR 1.25, 95% CI 1.04 to 1.52, p=0.02). Moreover, anxiety was not significantly associated with mortality risk after adjusting for depression (adjusted RR 0.88, 95% CI 0.66 to 1.17, p=0.37).Conclusions Anxiety is associated with increased risk of mortality and MACEs in patients with ACS. However, at least part of the association may be confounded by concurrent depressive symptoms in these patients.